Envelhecimento artificial, osmocondicionamento e estresse osmótico em sementes de sorgo: parâmetros fisiológicos, bioquímicos e citoquímicos - Oliveira, Alexandre Bosco de (2010)
This research was carried out in order to obtain basic data that can help them understand the physiological, biochemical and cytochemical responsible for the deterioration of aged seeds, reinvigoration of those primed and inhibition of germination and seedling establishment of sorghum under salt stress and study some of the mechanisms of adaptation to stress. The first chapter studies the effects of water stress (0, -0.2, -0.4 and -0.8 MPa) and saline (0, 75, 150 and 300 mM NaCl) on germination and seed vigor two genotypes of sorghum (CSF 18 and CSF 20). In the second and third chapter, to assess the quality of the seeds in the laboratory and the establishment of sorghum seedlings in the field, respectively, used a completely randomized design with four replications and a 2 x 2, consisting of four treatments: 1. aged seeds, 2. aging seeds 3. aged seeds and osmotically conditioned and 4. aging seeds and osmotically conditioned. In the fourth study we evaluated the water uptake, germination and early growth of seedlings derived from seeds aged, primed and under salt stress (0, 100, 200 or 300 mM NaCl). In the fifth chapter cytochemical tests were performed on seeds of sorghum subjected to the treatments described in the fourth chapter, but under a salinity of only 100 mM. The same treatments were used in the sixth chapter to evaluate the effect of these factors on seedling establishment, absorption of ions, organic solutes accumulation, lipid peroxidation and changes in enzymatic antioxidant system in seedlings grown in hydroponics in the presence or absence of NaCl. The sorghum genotypes show differential tolerance to osmotic stress caused by PEG-6000 and by NaCl, and the sensitivity to them varies depending on the stage of plant development. The artificial aging and salt stress promote adverse effects on germination, vigor and stand establishment of sorghum, which can be partly alleviated by the technique of priming seeds. Salt stress leads to significant reductions in the quality of the seeds and early growth of sorghum seedlings, causing some cytochemical changes in the seeds and various biochemical and physiological changes in seedlings under hydroponic cultivation.